Implementation of ISO 9001:2015 Quality Management System in Public Services: A Case Study on the Role of Leadership, Organizational Culture, and Human Resource Competence in the BMKG Work Unit of the Pattimura Meteorological Station, Ambon - Margaretha Titaley; Christina Sososutiksno; Salomi J. Hehanussa (LP2M IAIN Palopo, 2026)
This study aims to analyze the implementation of the ISO 9001:2015 Quality Management System (QMS) at the BMKG Pattimura Meteorological Station in Ambon and examine the role of leadership, organizational culture, and human resource competencies in supporting the effectiveness of quality system implementation. The study used a qualitative approach with a case study type. Research informants consisted of leaders, the QMS team, operational staff, and administrative staff who were selected purposively. Data collection techniques were carried out through in-depth interviews, observations, and documentation studies. Data analysis used the interactive model of Miles, Huberman, and Saldaña which includes data reduction, data presentation, and conclusion drawing. The results of the study indicate that the implementation of ISO 9001:2015 has been running effectively through the application of SOPs, internal audits, quality documentation, and continuous improvement actions. Leadership plays a dominant role in the success of implementation through commitment, resource provision, and periodic evaluations. Organizational culture supports the implementation of the quality system through work discipline, adherence to procedures, and public service orientation, although it still tends to be administrative. HR competencies are technically adequate, but understanding related to risk-based thinking and continuous improvement still needs to be improved. This study confirms that the implementation of ISO 9001:2015 not only functions as an operational quality standard, but also as an instrument for management control and strengthening public service accountability.